2013
DOI: 10.1186/2050-6511-14-14
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, pharmacokinetics and pharmacodynamics of GSK2239633, a CC-chemokine receptor 4 antagonist, in healthy male subjects: results from an open-label and from a randomised study

Abstract: BackgroundThe CC-chemokine receptor 4 (CCR4) is thought potentially to play a critical role in asthma pathogenesis due to its ability to recruit type 2 T-helper lymphocytes to the inflamed airways. Therefore, CCR4 provides an excellent target for anti-inflammatory therapy.MethodsThe safety, tolerability, pharmacokinetics and pharmacodynamics of the CCR4 antagonist GSK2239633, N-(3-((3-(5-chlorothiophene-2-sulfonamido)-4-methoxy-1H-indazol-1-yl)methyl)benzyl)-2-hydroxy-2-methylpropanamide, were examined in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 38 publications
(29 reference statements)
0
59
0
1
Order By: Relevance
“…30 Furthermore, there is growing interest in the development of small-molecule CCR4 antagonists as potential therapies against systemic inflammatory conditions such as asthma. [31][32][33] It has also been suggested that targeting T-lymphocyte infiltration may improve outcome after TBI, based on an experimental model. 34 Whether the overall role of MDC in human TBI is beneficial or detrimental remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, there is growing interest in the development of small-molecule CCR4 antagonists as potential therapies against systemic inflammatory conditions such as asthma. [31][32][33] It has also been suggested that targeting T-lymphocyte infiltration may improve outcome after TBI, based on an experimental model. 34 Whether the overall role of MDC in human TBI is beneficial or detrimental remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Продолжается его изучение при других опухо-лях [10]. Другие препараты этой группы находятся в процес-се разработки [11]. Другим хемоаттрактантом, который может быть мишенью противоопухолевой терапии, является простагландин Е 2 (PgE2).…”
Section: снижение рекрутинга иммуносупрессивных клеток в ткань опухолиunclassified
“…CCR3 and CCR4 act as receptors for a variety of chemokines including the eotaxins CCL5, CCL17, and CCL22, which play a role in asthma pathophysiology [23]. There is evidence that CCR3 inhibition may decrease inflammation, and CCR4 is believed to be able to recruit T H 2 cells to inflammatory sites [24]. CCR4 ligand binding induces the production and release of many cytokines [25] including granulocyte-macrophage colony-stimulating factor (GM-CSF) [26].…”
Section: The Pathophysiology Of Asthmamentioning
confidence: 99%
“…GSK2239633 [N-(3-[(3-[5-chlorothiophene-2-sulfonamido]-4-methoxy-1H-indazol-1-yl)methyl]benzyl)-2-hydroxy-2-methylpropanamide] is a potent CCR4 antagonist that acts by inhibiting CCR4-TARC (thymus and activation-regulated chemokine) binding and interrupting downstream signaling cascades [24]. The drug is currently in phase I trials.…”
Section: Drugs Targeting Ccr3 and Ccr4mentioning
confidence: 99%
See 1 more Smart Citation